VO #034 Supply installation, testing & commissioning of lighting protection system (rev.01) - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding VO #034 supply installation, testing & commissioning of lighting protection system (rev.01) of BRAC University new campus project.